Analisis Manajemen Operasional Terhadap Pertumbuhan Ekonomi Bengkel HRA Pada Masa Pandemi Covid-19 dan Setelah Pandemi Covid-19 - Arsalan bintang romadi; Adi Mansah (CV Edujavare Publishing, 2024)
The aim of this research is to identify the impact of the pandemic on the workshop business and analyze operational management on workshop growth after the Covid19 pandemic at the JL location. Cirendeu Raya No.2 East Ciputat, South Tangerang Ciputat. This research uses qualitative methods and the main data is obtained through interviews with HRA workshop business owners. Due to the Covid-19 pandemic, HRA Workshop experienced a significant decline in income, and they faced various problems in marketing and sales. However, they are also trying to find marketing alternatives, secure capital and assets, and understand digital technology for promotion.